Distinct HR expression patterns significantly affect the clinical behavior of metastatic HER2+ breast cancer and degree of benefit from novel anti‐HER2 agents in the real world setting. Issue 7 (7th August 2019) - Pizzuti, Laura; Krasniqi, Eriseld; Barchiesi, Giacomo; Della Giulia, Marina; Izzo, Fiorentino; Sanguineti, Giuseppe; Marchetti, Paolo; Mazzotta, Marco; Giusti, Raffaele; Botticelli, Andrea; Gamucci, Teresa; Natoli, Clara; et al.
Abstract : We analyzed data from 738 HER2‐positive metastatic breast cancer (mbc) patients treated with pertuzumab‐based regimens and/or T‐DM1 at 45 Italian centers. Outcomes were explored in relation to tumor subtype assessed by immunohistochemistry (IHC). The median progression‐free survival at first‐line (mPFS1) was 12 months. Pertuzumab as first‐line conferred longer mPFS1 compared to other first‐line treatments (16 vs . 9 months, p = 0.0001), regardless of IHC subtype. Median PFS in second‐line (mPFS2) was 7 months, with no difference by IHC subtype, but it was more favorable with T‐DM1 compared to other agents (7 vs . 6 months, p = 0.03). There was no PFS2 gain in patients with tumors expressing both hormonal receptors (HRs; p = 0.17), while a trend emerged for tumors with one HR ( p = 0.05). Conversely, PFS2 gain was significant in HRs‐negative tumors ( p = 0.04). Median overall survival (mOS) was 74 months, with no significant differences by IHC subtypes. Survival rates at 2 and 3 years in patients treated with T‐DM1 in second‐line after pertuzumab were significantly lower compared to pertuzumab‐naïve patients ( p = 0.01). When analyzed by IHC subtype, the outcome was confirmed if both HRs or no HRs were expressed ( p = 0.02 and p = 0.006, respectively). Our results confirm that HRs expression impacts the clinical behavior and novel treatment‐related outcomes of HER2‐positive tumors when treatment sequences are considered. Moreover, multivariate analysis showed that HRs expression had no effect on PFS and OS. Further studies are warranted to confirm our findings and clarify the interplay between HER2 and estrogen receptor pathways in HER2‐positive (mbc) patients. Abstract : What's new? About half of breast cancers positive for human epidermal growth factor (HER2) also express hormone receptors but the impact of hormone receptor status on the success of HER2‐directed treatments is not fully explored. Here the authors retrospectively assessed tumor behavior and treatment outcomes in 738 women with HER2+ metastatic breast cancer treated with new generation anti‐HER2 agents. Distinct hormone receptor expression patterns significantly affected the progression free and overall survival, justifying further studies to define optimal treatment regimens and the interplay between hormone receptor and HER2 signaling.